Distribution and Abundance of Fish Larvae in South of Alas Strait, West Nusa Tenggara - Irwan Jatmiko; Fathur Rochman; Gussasta Levi Arnenda (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2018)
The early life of fish larvae is important to understand the entire life history of the fish. At this phase, larvae movement is very weak and dependent on the movement of water currents. This study aims to determine the distribution and abundance of fish larvae in the waters south of the Port of Tanjung Luar, West Nusa Tenggara, Indonesia. Sampling of fish larvae were done at five stations at waters around Alas Strait and Indian Ocean south of East Lombok. Sampled were collected from 5 different depth: 0-200 m, 201-1000 m, 1001-2000 m, 2001-3000 m and >3000 m. A total of 122 fish larvae were collected which belong to 26 families and varied compositions among observation stations. The samples was dominated by Scombridae family (18 %), followed by Carrangidae and Blenniidae (13.1% and 6.6%, respectively). The highest abundance was occurred in station V (0-200 m) of 125 individuals.1000-1m3. It showed that inshore/shallow waters have more abundance than offshore/deep waters. The findings from this study can be basic information for the authorities to establish sustainable fisheries policy. Keywords: fish, larvae movement, sustainable fishery, early life.